Optimizing Education Through Website-Based Learning Media: Implementation in Junior High Schools - Utami, Listia; Andri Majid; Bobur Sobirov; Jaffer Basha (Yayasan Cendekiawan Digital Indonesia (CEDDI), 2024)
This study aims to design and implement a website-based learning and information management system for MTs KSM Kalupapi. The system serves as a comprehensive platform for facilitating school information dissemination and supporting online learning processes. Employing the UML approach, the system was developed with intuitive interfaces and structured data management to ensure accessibility and functionality for diverse user groups. It accommodates school principals for administrative oversight, teachers as content managers, students for accessing educational materials and assignments, and parents for monitoring their children's academic progress. The system underwent rigorous testing using the black box method to validate its functionality, ensuring accurate outputs aligned with specified requirements. Survey feedback from users indicated exceptional satisfaction, with an average score of 99% and overwhelmingly